Production of TNF-alpha by skin explants of dinitrochlorobenzene-challenged ears in rats: A model for the evaluation of contact hypersensitivity - Kataranovski Milena; Kandolf-Sekulović Lidija; Milosavljević Ivica (Vojnosanitetski Pregled)
Background. Contact hypersensitivity (CHS) is a local inflammatory response of the skin following challenge of hapten-sensitized animals. It is the consequence of cell infiltration of derm and the release of inflammation mediators, among which Tumor necrosis factor-alpha (TNF-α) is one of the most important factors. The intensity of the inflammation could be quantified by ear swelling which is the classical manifestation of the reaction. This study was testing the working hypothesis that levels of TNF-α in skin organ culture medium should correlate with the intensity of CHS reaction measured in vivo by ear swelling assay, and with the density of dermal infiltrate in ear skin samples. In order to test the working hypothesis, the intensity of inflammatory reaction following challenge was evaluated by classical measurements of ear swelling, by the determination of TNF-α levels in culture fluids of ear skin following epicutaneous application of dinitrochlorobenzene (DNCB) into the ears of sensitized animals. Methods. Animal model of CHS reaction to DNCB in Albino Oxford rats was used as described. Ear swelling was quantified in percentage terms as the difference in thickness between the challenged and nontreated ears of the same animal. Dermal infiltrate density in histopathologically analyzed samples of ear skin was evaluated by computer-assisted image analysis. Ear skin samples were cultured in standard medium for 24 h, and TNF-α concentration in the conditioned medium was subsequently determined with ELISA test. Results. Dose-dependent increase in the density of the dermal infiltrate and in TNF-α in CM were noted following the application of 0.65%, 1.3% and 2.6% of DNCB to the ears of previously sensitized rats. The correlation between ear swelling and the levels of TNF-α (r=0.933, p<0.001) in CM, and between ear swelling and dermal infiltrate density (r=0.916, p<0.001) was found. Correlation was also found between the density of the dermal infiltrate and the levels of TNF-α (r=0.865, p<0.001). Conclusion. Presented data suggested that skin-organ culture system and the quantification of inflammatory mediators might be used for the evaluation of contact hypersensitivity reaction and its intensity.